Improved Seedling Quality of Polybag Plants of Albizia procera - Use of Mounted Angle Iron Beds - Gera, Mohit; Gera, Neelu; Bhandari, A. S.; Pant, N. C. (Indian Forester, 2000)
A trial was carried out to study the effect of polybag size and number of perforations at the bottom on different seedling growth and quality parameters in case of Albizia procera seedlings raised on Mounted Angle Iron beds. Highly significant differences in seedling growth parameters viz., height, collar diameter, length oftap root, root and shoot biomass, and seedling quality parameters viz. sturdiness, root/shoot ratio, number of nodules and ratio of secondary + tertiary root biomass to total ropot biomass, were observed among different treatments. The treatment T3 (Polybag size 23 x 11 cm with 4 perforations at bottom) performed the best in respect of seedling growth parameters with height 81.33 cm, collar diameter 0.76 cm, length of tap root 16.90 cm, shoot biomass 14.36 gm and root biomass 11.67 gm. However the treatment T12(Polybag size U x 6 cm with 6 perforations at bottom) recorded best values for most of the seedling quality parameters viz. sturdiness 82.03, root/shoot ratio 1.21 and ratio of secondary + tertiary root biomass to the total root biomass 0.44.